Irish linen laws and proposed amendments thereof - Bates, Arthur Henry (Statistical and Social Inquiry Society of Ireland, 1881)
The custom, largely adopted in many manufacturing districts, particularly in the north of Ireland, of manufacturers in the linen and damask trade giving out to weavers the materials for webs to be woven by them in their own homes, has been the origin of a small code of laws. The fact that property, representing a very large amount of capital, is entrusted during a considerable time to men generally poor, and is left during that time under their complete control, in danger of being lost or injured, not only by their dishonesty but also by their want of care or of industry, or even by their misfortunes, as well as by the dishonesty, negligence, or misfortune of the other inmates of their houses, has been considered sufficient to justify the existence of special laws, containing provisions intended to protect the interests of the owners of such property. These provisions, with others regulating the sale of flax and linen, and intended to protect buyers of such against fraud, form the contents of the Acts which are the subject of this paper.
Read before the Society, 25 January 1881
Keywords: Irish linen laws; Manufacturing; Linen industry; Small businesses; 314.15